Figures of the world : the naturalist novel and transnational form - Hill, Christopher L., 1964- (FlashPoints (Evanston, Ill.), 2020)
"Hill's analysis shows that transnational literary studies must operate on multiple scales, combine distant reading with close analysis, and investigate how literary forms develop on the move"--